Pitfalls in the European Enlargement Process: Financial Instability and Real Divergence - Helmut Wagner (Deutsche Bundesbank, 2002)
Many of the EU accession countries have announced that they will not only try to enter the EU as quickly as possible but also to adopt the euro at an early date. This is justified by the effort to avoid the danger of financial instability in the period prior to euro-introduction. However, by trying to avoid this danger, the CEECCs, at least the (economically, institutionally and technologically) less developed, may run into another danger or pitfall, namely of real divergence (or very slow real convergence). The paper investigates these dangers or pitfalls. It argues that for some accession countries the costs of entry at an early date may be very high, and that there may also be negative spillovers for the other accession countries and for the EU core countries. – – Viele der EU-Beitrittsländer haben angekündigt, dass sie nicht nur der EU, sondern auch der EWU schnell beitreten wollen. Dies wird damit begründet, dass so die Gefahr finanzieller Instabilität in der Zeit vor der Euro-Einführung verringert wird. Dies kann allerdings die Beitrittsländer (zumindest die ökonomisch, institutionell und technologisch schwächer entwickelten) in eine andere Gefahr stürzen, nämlich die anhaltender realer Divergenz (oder nur sehr langsamer Konvergenz). Der Aufsatz analysiert diese Gefahren oder Fallstricke der E(W)U-Erweiterung. Es wird argumentiert, dass die Kosten eines (zu) frühen EWU-Beitritts für einige der Beitrittsländer sehr hoch sein können, und dass auch Spillover-Kosten für die anderen Beitrittsländer und für die EU-Kernländer auftreten.
Keywords: E5; F4; P2; 330; European Integration; Transition Economies; Monetary Policy; Financial Instability; Real Convergence; Anticipatory Recession; EU-Erweiterung; Finanzmarktkrise; Europäische Wirtschafts- und Währungsunion; Entwicklungskonvergenz; Kosten-Nutzen-Analyse; Übergangswirtschaft; Osteuropa